Driving Factors of Passenger Transport - Gerard C. de Jong; Odette van de Riet (European Journal of Transport and Infrastructure Research, 2008)
Over the past few decades passenger transport has grown rapidly resulting in a multitude of problems including severe traffic congestion and pollution. It is expected that passenger transport will continue to grow rapidly in the future, which will worsen the situation even further. The traditional approach to deal with the problems is to expand the infrastructure. However, transport policy is a broad and versatile field. Many different types of policy measures can be observed in literature and practice. Sound transport policy-making requires knowledge on the drivers of transport demand This article is aimed at (re)structuring the many different insights in a single conceptual model, which reviews the key drivers, and how each affects the various choices that travellers make (activity type, destination, mode, time-of-day and route) and the resulting impact on overall passenger transport demand. The model was derived on the basis of a review of literature, which was supplemented by a review of thirteen exemplary urban area cases. In addition, a quantitative data analysis was carried out to assess the transport demand elasticities for various drivers. Current study has been carried out in response to the search for effective transport policy, which is discussed in the concluding section. The outcomes are of particular relevance of policy analysts and policy makers developing passenger transport policy, but are also useful for scholars and students in the field of transport.